2018
DOI: 10.4314/jasem.v21i7.8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of the differential equation for simulation of the rice blast disease

Abstract: ABSTRACT:Rice blast disease is one of the diseases that causes damage to rice yield in Thailand. This research aims to simulate the severity of rice blast disease using the EPIRICE model for Khao Dawk Mali 105 that caused by Pyricularia oryzae in Prachin Buri, Thailand, and evaluate the simulation results by comparing with field collection data using root mean square error (RMSE). The epidemiological model consists of a system of ordinary differential equations (ODEs) that describes the dynamic of rice leaf di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Considering all these factors, we found that the EPIRICE model from our previous study closely met most of the abovementioned requirements ( Kim et al, 2015 ). Because of its broad genericity and simplicity but sound infection algorithms, EPIRICE has been adopted in many modeling-based studies worldwide ( Duku et al, 2016 ; Hensawang et al, 2017 ; Kim and Cho, 2016 ; Kim et al, 2015 ; Sittisak et al, 2017 ). In this respect, our objective was to develop an SCF-compatible disease epidemiological model by extracting and modifying the core infection algorithms of the EPIRICE model.…”
mentioning
confidence: 99%
“…Considering all these factors, we found that the EPIRICE model from our previous study closely met most of the abovementioned requirements ( Kim et al, 2015 ). Because of its broad genericity and simplicity but sound infection algorithms, EPIRICE has been adopted in many modeling-based studies worldwide ( Duku et al, 2016 ; Hensawang et al, 2017 ; Kim and Cho, 2016 ; Kim et al, 2015 ; Sittisak et al, 2017 ). In this respect, our objective was to develop an SCF-compatible disease epidemiological model by extracting and modifying the core infection algorithms of the EPIRICE model.…”
mentioning
confidence: 99%